Section Three: Solving Multi-Step Equations (7 of 10)

​  n−3n=14−4nn−3n=14−4n

1 answer

To solve the equation \( n - 3n = 14 - 4n \), let's first simplify both sides.

  1. Combine like terms on the left side:

    \[ n - 3n = -2n \]

    So the equation now reads:

    \[ -2n = 14 - 4n \]

  2. Next, we'll add \( 4n \) to both sides to isolate the variable \( n \). This gives us:

    \[ -2n + 4n = 14 \]

    Simplifying the left side:

    \[ 2n = 14 \]

  3. Now, divide both sides by 2 to solve for \( n \):

    \[ n = \frac{14}{2} = 7 \]

Thus, the solution to the equation \( n - 3n = 14 - 4n \) is

\[ \boxed{7}. \]

Similar Questions
  1. ELEMENTARY ALGEBRA #3Page 23 Chapter 3 Lesson 3.02 Solving Multi-step Equations Reading Assignment: Study pages 126 – 129
    1. answers icon 4 answers
  2. 7.3.6 - Quiz: Solving Multi-Step Equations QuizAlgebra Readiness (Pre-Algebra) A / 7. Equations and Inequalities / 7.3. Solving
    1. answers icon 9 answers
    1. answers icon 1 answer
  3. We're doing multi-step equations, and I need help on how to check my answers?I knew how to do it on two-step equations, but now
    1. answers icon 1 answer
more similar questions